Visual Arts Based on Artistic Form Aspects of Local Design on Mbaru Niang Traditional Houses - Sanatra, Anja Bany; Pramana, Dwiki Yudha; Yuliasari, Indah (Cultural Syndrome, 2021)
Abstract. Indonesia has rich local wisdom and is worth preserving since it is an archipelagic nation with a diverse population of ethnic and cultural backgrounds. The identity and even the cultural character of an area in Indonesia are shown via the existence of Indonesian architecture. Because of this, traditional dwellings differ greatly throughout Indonesia, with unique features seen in each location. A traditional home in Flores called Mbaru Niang is one of them. Indonesian residential architecture has adapted effectively to the country's current climate. Local values are often emphasized in folk architecture, sometimes referred to as vernacular architecture. This distinguishes it from other architectural forms and reflects the knowledge of the place. Mbaru Niang, residing in Waerebo, serves as a study subject. After that, the information was examined to determine the traditional house's architectural idea depending on its location. It is also anticipated that the building idea would provide Indonesia with a workable, hygienic, and ecologically beneficial option for contemporary structures. Keywords: Artistic Design, Concepts, Folk Architecture